Alat Peraga Pembelajaran Fisika untuk Menentukan Intensitas Bunyi: A Literature Review - Analiatus Shofiyah; S. Ida Kholida MS; Maimon Sumo; Riskiyana Vajari; Moh. Nawafil Zain Robiz; Ferdi Wahyudi (PT. PENERBIT TIGA MUTIARA, 2024)
This study aims to create and implement a physics learning visualization tool that can be used to determine sound intensity. This teaching aid is designed to help students understand physics concepts related to sound waves and their measurements in a more interactive and practical way. The research method used was a review of 20 articles. The results of literature studies can help students better understand the concept of sound intensity. They have the ability to directly see changes in sound intensity through interactive teaching aids. Based on the research results, it was concluded that this physics learning aid not only helps in learning the concept of sound intensity, but also increases students' motivation and interest in learning. The use of teaching aids/visualization is recommended in physics education at the upper secondary education level or equivalent, as an innovative and efficient learning medium.